(untitled) (International Journal of Engineering Materials and Manufacture, 2020)
The scientists revise the heat transfer enhancement techniques time to time to achieve better performance and to obtain optimized designs of heat exchangers. The present study reviews the performanceÂ and techniques of heat transfer enhancement using various insert devices such as twisted tape and wire coil insert as well as completely differentÂ forms of otherÂ inserts like air-foil shape inserts, X-shaped twisted tape inserts, baffles and V-winglets insertsÂ with various types of medium and nanofluids. According to the summary of recent significantÂ researchesÂ on the heat transfer enhancement byÂ usingÂ different types of Â inserts and combinations of these inserts with various nanofluids showed that insert can indicatively enhance the heat transfer rate by modifying its geometry or configurations like twist ratio, length ratio, pitch ratio, segmented tape, perforated tape, angle of arrangements and insert quantities and so on which caused a considerable impact on performance characteristics of heat transfer enhancement along with the pressure drop and friction factor. It is revealed through reviewing the related literature that the highest value of equivalence heat transfer enhancement is as maximum as 400%, 300% and 9% for the twisted tape insert with helical tube, the air foil shaped inserts and for the wire coil inserts, respectively when compared with the smooth tube. In the case of baffles in nanofluids, as maximum as 255% equivalence heat transfer enhancement could be achieved when compared with that of baffles without nanofluids.